Integrating E-Comics and Problem-Based Learning (PBL) to Foster Higher-Order Thinking Skills in Elementary Students - Mazwar Ismiyanto; Sofyan Anif; Ahmad Muhibbin (International Electronic Journal of Elementary Education, 2026)
The demands of 21st-century education necessitate that students develop Higher Order Thinking Skills (HOTS) to thrive in a dynamic and complex digital era. Nevertheless, elementary-level instruction frequently remains dominated by conventional approaches that inadequately foster critical, creative, and problem-solving competencies. Technology-based learning innovations offer a promising solution, particularly through the integration of E-Comics with Problem-Based Learning (PBL). This study examines the effectiveness of combining E-Comics and PBL to enhance higher-order thinking skills among elementary school students. A quasi-experimental design was employed, utilizing both control and experimental groups. Participants comprised fifth-grade students from two elementary schools in Surakarta, Central Java, Indonesia. Research instruments included HOTS-aligned assessments and structured classroom observation sheets. Data were analyzed using descriptive statistics and inferential t-tests. Results demonstrated that the experimental group, taught using the E-Comic-PBL integration, exhibited a statistically significant improvement (p<0.05) in higher-order thinking skills compared to the control group. These findings indicate that integrating interactive digital media such as E-Comics with PBL can serve as an innovative strategy to cultivate students' critical thinking, creativity, and problem-solving abilities. Pedagogical implications and recommendations for further research are also discussed.